A gênese do arquivo fotográfico de Sebastião Leme: uma leitura da acumulação - Lima, Maria de Lourdes [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The genesis and the accumulation of Sebastião Leme's photographic archive are located in one of the extremities of the internal flows of information, designed as channels through where the information spreads in the circuit of the institutions with competence to administer it. Therefore, it is in the left extremity that is located the place of the creation of the information, from a copyright point of view, released, then, of the dynamics where the constituent internal flows of information of the institutional spaces of information are operated. Thus, the qualification of space is the ability they have to overcome their own limits of organization, retrieval and access of information, in public scale. The problem consists of the existence of a archive of images, restricted just to the personal cycle, as exclusive reference of the family affectionate memory, indistinct and tied to their precarious condition of informational support, in a state of latency. Which brings us to formulate the hypothesis that the photographic archive - as genesis and accumulation - requires that its passage is from the personal context to the public sphere, which implies the recognition of its condition of information that is only effective when absorbed by the flow of information.It is when this file will fulfill its existential and informational function, as representation and value. The theoretical and methodological frameworks of research, in the context of information science, lead us to: 1) examine the photographic image at the moment of its genesis, based on its index, icon and symbolic representation, from the point of view of its condition of visual information, 2) consider the photography as a process of individual creation, that expressed its starting from an accumulation that can also join other production types, to example of the testimony and of the autobiographical textual narrative... (Complete abstract click electronic access below)

A gênese e a acumulação do arquivo fotográfico de Sebastião Leme estão localizadas em uma das extremidades dos fluxos internos de informação, concebidos enquanto canais por onde a informação se propaga no circuito das instituições com competência para administrá-la. Portanto, é na extremidade esquerda que está localizada o lugar da criação da informação, do ponto de vista autoral, desvinculado, pois, da dinâmica onde se operam os fluxos internos de informação constitutivos dos espaços institucionais de informação. Logo, a qualificação de espaço se deve à capacidade que eles têm de superação de seus próprios limites de organização, recuperação e acesso da informação, em escala pública. O problema consiste na existência de um arquivo de imagens, restrito apenas ao ciclo pessoal, como referência exclusiva da memória afetiva familiar, indistinto e atado a sua precária condição de suporte informacional, em estado de latência. O que nos leva a formular a hipótese de que o arquivo fotográfico – enquanto gênese e acumulação − requer que a sua passagem se dê do âmbito pessoal para a esfera pública, o que implica o reconhecimento da sua condição de informação que só se efetiva quando for absorvido pelos fluxos de informação. É quando esse arquivo passará a cumprir a sua função existencial e informacional, como representação e valor. Os enquadramentos teóricos e metodológicos da pesquisa, no âmbito da ciência da informação, nos levam a: 1) examinar a imagem fotográfica, no instante da sua gênese, com base na sua representação indiciária, icônica e simbólica, sob o ponto de vista da sua condição de informação visual; 2) considerar a fotografia como um processo de criação individual, que se expressa a partir de uma acumulação que também pode agregar outros tipos de produção, a exemplo do testemunho...
Keywords: Leme, Sebastião; Fotografia; Ciência da informação; Arquivo fotográfico; Genesis; Photographic Archive; Creation of the information; Machine of 360°